Penerapan Teknik Relaksasi Nafas dalam Upaya Menurunkan Tekanan Darah pada Lansia Penderita Hipertensi di Desa Mipitan Kelurahan Mojosongo - Cantika Nur Cahyani; Dewi Kartika Sari (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Background : In old age, there is a decline in the body's immune function, including a decline in heart function, one of the diseases of which is hypertension. Hypertension is high blood pressure with systolic blood pressure results >140 mmHg or diastolic blood pressure ≥ 90 mmHg.. The prevalence of hypertension cases according to the Surakarta City Health Service showed an increase in the incidence of hypertension in 2023 reaching 67,355 cases. One of the non-pharmacological therapies that can be used is deep breathing relaxation techniques. Objective: This study describes a comparison of blood pressure development before and after the application of deep breathing relaxation techniques. Method: This study used a case study of 2 respondents conducted on May 11-13, 2024 for 2 times in a row with a therapy duration of 10 minutes. Results: The application of Deep Breathing Relaxation Therapy to both respondents obtained comparative results of development before and after therapy in Mrs. S systolic 24 MmHg and diastolic 17 MmHg while Mrs. T showed a decrease with systolic 25 MmHg and diastolic 13 MmHg. Conclusion: The results of the study can be concluded that there is an effect of deep breathing relaxation techniques on reducing systolic and diastolic blood pressure in both respondents.